Architecting Virality: Information Sharing from Government FB Page to Netizens - Afdallyna Fathiyah Harun; Siti Nuradzarul Aqmaar Adzman; Fauzi Mohd Saman; Saiful Izwan Suliman (Institute of Advanced Engineering and Science, 2018)
In accordance with e-government initiatives, many ministries in Malaysia have engaged content to public using social media for better two-way communications. However, creating an online presence is not necessarily easy as digital content consumers are often bombarded with information and those that fail to capture information will be rendered uninteresting and irrelevant. This is imperative as for most part, users are in control of where they allocate attention and what they share. Using virality as a context, it is opined that information content that are well-designed will trigger specific information and propel the sharing of that information over the Internet. A study employing FB post categorization and sharing motivations survey was carried out in the context of Ministry of Health Malaysia Facebook page. The findings show that users are inclined towards Infographics with various sharing motivations. The results can be used by Malaysian ministries on how best to design and disseminate information for the benefit of the netizens on social media sites.